2019
DOI: 10.1097/rct.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adaptive Statistical Iterative Reconstruction-V Reconstruction Algorithm vs Filtered Back Projection in the Detection of Hypodense Liver Lesions: Reader Performance and Preferences

Abstract: Objective The aim of the study was to evaluate diagnostic accuracy and readers' experience in the detection of focal liver lesions on computed tomography with Adaptive Statistical Iterative Reconstruction-V (ASIR-V) reconstruction compared with filtered back projection (FBP) scans. Methods Fifty-five patients with liver lesions had FBP and ASIR-V scans. Two radiologists independently reviewed both sets of computed tomography scans, identifying and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…However, the SNR was considerably higher than the FBP reconstructed image ( P < 0.05). These results were consistent with the research conclusions of Dimmitt et al (2019) [ 21 ]. It was proved that the noise of the CT image reconstructed by the ASIR model was considerably reduced, the image quality was improved, and the advantages of image quality and lesion detection were obvious.…”
Section: Discussionsupporting
confidence: 94%
“…However, the SNR was considerably higher than the FBP reconstructed image ( P < 0.05). These results were consistent with the research conclusions of Dimmitt et al (2019) [ 21 ]. It was proved that the noise of the CT image reconstructed by the ASIR model was considerably reduced, the image quality was improved, and the advantages of image quality and lesion detection were obvious.…”
Section: Discussionsupporting
confidence: 94%
“…Its significance lies in obtaining the image of the internal structure of the detected object without causing any physical damage to the object. Due to its considerable advantages, it has shown unique importance in various application fields [ 17 19 ]. For example, it has many applications in medical radiology, nuclear medicine, electron microscopy, radio radar astronomy, light microscopy, holographic imaging, and theoretical vision.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have demonstrated that subjective image quality does not necessarily correlate with increased diagnostic accuracy; in fact, IR does not preserve low-contrast detectability, and there is wide variability in low-contrast detection among different IR methods for the different dose levels. 4,60 Dimmitt et al 52 evaluated the diagnostic accuracy of liver lesion detection using ASiR-V in comparison with FBP and demonstrated that ASiR-V is objectively superior to FBP, despite the readers having better identified liver lesion with FBP. Therefore, readers should adequately train to avoid any misdiagnosed liver lesions.…”
Section: Clinical Applications Oncological Applicationsmentioning
confidence: 99%